Optimal treatment strategies for musculoskeletal diseases - Haugen, Kjetil K. (Vysoké učení technické v Brně, Fakulta strojního inženýrství, Ústav matematiky, 2013)
This paper presents a model which aims to find an optimal treatment time for patients with musculoskeletal diseases. The stochastic dynamic programming model presented is based on minimizing expected costs given a stochastic processes for cure with and without treatment as well as costs for treatment and reduced quality of life as a consequence of the disease. The main results derived in the paper include explicit conditions for an interior optimal solution and a simple and intuitive approximate solution. Even though the presented model is specifically aimed at musculoskeletal dis- eases, the model’s generality should make it applicable for a wide range of disease treatment strategies.